EXPRESSION OF TOLL LIKE RECEPTOR 2 AND TOLL LIKE RECEPTOR 4 IN CHRONIC PERIODONTITIS BY INDIRECT IMMUNOFLUROSCENCE - Romaladin, D’Souza; Kishore G, Bhat; Ramakant, Nayak; Sailaj, D (International Journal of Clinical and Biomedical Research, 2016)
Aim: The aim of the present study was to analyze the expression level and localization of Toll-like receptor 2 and Toll-like receptor 4 in gingival samples of healthy and chronic periodontitis subjects by indirect immunofluorescence technique. Methods: Gingival tissue samples were obtained from 25 healthy individuals and 25 chronic periodontitis patients. The tissues were processed and the initial characterization was done by H&E staining. Indirect immunofluorescence technique was then performed to detect TLR2 and TLR4. Immunofluorescence images were acquired and quantitative expression of TLRs was analyzed by calculating the percentage of cells showing positive results. Results: TLR2 and TLR4 expression in healthy gingival tissues were lower than in the tissues of patients with periodontitis. In patients with periodontitis both TLR2 and TLR4 expression was slightly higher in epithelium as compared to their expression in connective tissue. Conclusions: The results suggest that TLR2 and TLR4 in the gingival cells are stimulated by the bacterial products in the oral cavity and participate in the innate immune response against these organisms. KEYWORDS: Chronic Periodontitis; Gingival tissue; Immunofluorescence; TLR2 & TLR4.